Aktivitas antioksidan fikosianin Arthrospira platensis yang diekstrak menggunakan dimetil sulfoksida: Antioxidant activity of Arthrospira platensis phycocyanin extracted using dimethyl sulfoxide - Sunandar, Husna Vannisa; Husni, Amir (Jurnal Pengolahan Hasil Perikanan Indonesia, 2025)
Arthrospira platensis uses phycocyanin, its main pigment, for its antioxidant properties in the food and cosmetic fields. This study aims to determine the effect of biomass conditions on the characteristics (yield, phycocyanin concentration, purity index) and antioxidant activity of A. platensis phycocyanin extracted using dimethyl sulfoxide (DMSO). Wet and dry biomass of A. platensis were extracted using 50% DMSO with a ratio of 1:10 to obtain phycocyanin extract and then purified using ammonium sulfate. Phycocyanin extract and purified phycocyanin were analyzed for yield, concentration, purity index, functional groups, and antioxidant activity (1,1-diphenyl-2-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) methods). The results indicated that the conditions of A. platensis biomass (wet and dry) extracted using DMSO affected the characteristics of phycocyanin and antioxidant activity. Phycocyanin from wet biomass has characteristics (yield 145.14±5.59 mg/g, concentration 0.40±0.02 mg/mL, purity index 0.19±0.06) and antioxidant activity (IC50 DPPH 30,628.89±886.81 ppm, FRAP 1,695.57±5.18 μM/g) higher than that from dry biomass (yield 39.50±20.3 mg/g, phycocyanin concentration 0.08±0.04 mg/mL, purity index 0.03±0.02) and antioxidant activity (IC50 DPPH 162,820.59±1,446.30 ppm, FRAP 1,691.01±50.29 μM/g). Fourier transform infrared (FTIR) results show the typical absorption of functional groups found in phycocyanin. The antioxidant activity of phycocyanin from wet biomass using the DPPH method (primary antioxidant) is classified as a weak antioxidant, while based on the FRAP method (secondary antioxidant), the antioxidant is classified as a strong antioxidant.